Mosquitoland - Arnold, David, 1981- (Viking, an imprint of Penguin Group (USA), 2015)
"When she learns that her mother is sick in Ohio, Mim confronts her demons on a thousand-mile odyssey from Mississippi that redefines her notions of love, loyalty, and what it means to be sane"--